DINAMIKA KERAWANAN SOSIAL MENUJU KESEJAHTERAAN SOSIAL DI KOTA PEKANBARU - Rinaldi, Kasmanto (EDUTECH CONSULTANT, 2017)
Poverty is a complex problem seemed to be a perennial problem like a circle that has no end and always rotates growing and increasingly impacting Social luas.Dinas and Cemetery is an authorized agency in the welfare activities of social life masyarakat.Kewenangan social order that is part of the development in sosial.Kewenangan comprehensive welfare can be seen as an opportunity for the region to develop and commit itself for the sake of progress of the region, and on the other hand is a new challenge that is quite heavy and menantang.kurangnya plan as curbing targets that are less precise, the execution time is executed less precise in controlling the schedule, the absence of special shelters Psychotic Gelandagan or people with mental disorders were displaced and many other issues is a major obstacle that must be overcome.